2019
DOI: 10.31235/osf.io/yv2es
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistence of solid fuel use despite increases in LPG ownership: New survey evidence from rural north India

Abstract: Solid fuel use is an important contributor to air pollution and disease burden in India. We present survey evidence documenting LPG ownership and cooking fuel use in rural north India. LPG ownership has increased rapidly, substantially driven by the Ujjwala Yojana. Three-quarters of rural households in Bihar, Madhya Pradesh, Rajasthan, and Uttar Pradesh now have LPG. Almost all of these households also have a stove that uses solid fuels, and among those owning both, almost three-quarters used solid fuels the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…hinted heterogeneous results from their study areas, but mentioned that more people are switching to latrine use. [936] Roy and Pramanick while assessing the progress of sanitation in India have analyzed the interrelationships between SDG 6, SDG 3, and SDG 1. [37] Their study concluded with a positive impact of increasing per capita gross domestic product (GDP) on improving sanitation-related indicators, which in turn positively influence to reduce water and sanitation-related diseases, especially in children and aged population.…”
Section: Discussionmentioning
confidence: 99%
“…hinted heterogeneous results from their study areas, but mentioned that more people are switching to latrine use. [936] Roy and Pramanick while assessing the progress of sanitation in India have analyzed the interrelationships between SDG 6, SDG 3, and SDG 1. [37] Their study concluded with a positive impact of increasing per capita gross domestic product (GDP) on improving sanitation-related indicators, which in turn positively influence to reduce water and sanitation-related diseases, especially in children and aged population.…”
Section: Discussionmentioning
confidence: 99%
“…But the only viable public health strategy for reducing lung obstruction is prevention through the adoption of cleaner fuels. Existing government programs in India to promote cleaner fuels are means-tested, provide modest capital subsidies, involve significant private investments, do not have components for encouraging behavior change, and focus on private harms to women from cooking with solid fuels (Sethi and Deep, 2018;Gupta et al, 2019). There is a case for greater investments in efforts to communicate the private and neighborhood harms of solid fuel use and encouraging households to switch to cleaner fuels.…”
Section: Discussionmentioning
confidence: 99%
“…From an environmental health perspective, there is an urgent need for research that integrates social determinants, environmental exposures, measures of pollution, and respiratory health outcomes. Existing evidence points that women's lower status impedes the adoption of cleaner fuels (Kishore and Spears, 2014;Austin and Mejia, 2017;Gupta et al, 2019). Researching the role of gender in the persistence of solid fuel use in India, and investigating approaches that address this social determinant of adoption of cleaner fuels are an important research concern as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of this mission, as the world's largest sanitation campaign has prompted it to be replicated in other countries, for example the Clean Nigeria Campaign (GoN 2019). However, the plans of SBM did not go beyond the latrine, leaving the rest of sanitation service chain unattended and the sustainability of the outcomes in significant uncertainty (Kumar 2017;Gupta et al 2019).…”
Section: Introductionmentioning
confidence: 99%